Development of Student Worksheets for Chemistry Experiments Based on Socio-scientific Issues - Disa Putri Anggianti; Abdullah Abdullah; Herdini Herdini (Research, Training and Philanthropy Institution Natural Aceh, 2026)
Learning plays an essential role in shaping students' understanding, but many teachers still use conventional methods that are less varied, leading to less enjoyable and unmotivating learning, especially in chemistry subjects. The observations indicate a lack of teaching materials and chemical experiments that could improve students' understanding and motivation. This study aims to develop a valid Chemistry Experiment Student Worksheet for Grade XI that addresses socio-scientific issues and to examine user responses to the worksheet. The research model used is a 4-D model consisting of 4 stages: define, design, develop, and disseminate. The results of this study are in accordance with the assessments of 2 material expert validators and one media expert validator, namely the Chemistry Experiment Student Worksheet Based on Socio-Scientific Issue, which obtained percentages of 98.4375% and 100%, respectively, and were categorized as valid. This means that the Experiment Student Worksheet developed is suitable for use. The Student Worksheet for Chemistry Experiments Based on Socio-scientific Issue also received a positive response from users, with 92.96% and 87.91% of teacher and student responses, respectively, in the good category.